Never let go [videorecording (DVD)] - Ford, Howard J., 1973-; Dixon, Angela; Whitmey, Nigel; Eichhorn, Lisa, 1952- (Sony Pictures Home Entertainment, 2017)
A single mother desperately searches for her missing child in a beautiful, but unfamiliar land, following an apparent abduction. Trusting no one, and stopping at nothing, as she weaves her way through the murky backstreets and barren landscapes, now implicated in the murder of a seemingly innocent man, her connections back in the US begin to reveal that there is much more at stake than first meets the eye.